Did I find the right examples for you? yes no

# numpy.polynomial.hermite_e.hermemul

All Samples(4)  |  Call(4)  |  Derive(0)  |  Import(0)
Multiply one Hermite series by another.

Returns the product of two Hermite series `c1` * `c2`.  The arguments
are sequences of coefficients, from lowest order "term" to highest,
e.g., [1,2,3] represents the series ``P_0 + 2*P_1 + 3*P_2``.

Parameters
----------
c1, c2 : array_like
1-D arrays of Hermite series coefficients ordered from low to(more...)

def hermemul(c1, c2):
"""
Multiply one Hermite series by another.

Returns the product of two Hermite series `c1` * `c2`.  The arguments
are sequences of coefficients, from lowest order "term" to highest,
e.g., [1,2,3] represents the series ``P_0 + 2*P_1 + 3*P_2``.

Parameters
----------
c1, c2 : array_like
1-D arrays of Hermite series coefficients ordered from low to
high.

Returns
-------
out : ndarray
Of Hermite series coefficients representing their product.

--------

Notes
-----
In general, the (polynomial) product of two C-series results in terms
that are not in the Hermite polynomial basis set.  Thus, to express
the product as a Hermite series, it is necessary to "reproject" the
product onto said basis set, which may produce "unintuitive" (but
correct) results; see Examples section below.

Examples
--------
>>> from numpy.polynomial.hermite_e import hermemul
>>> hermemul([1, 2, 3], [0, 1, 2])
array([ 14.,  15.,  28.,   7.,   6.])

"""
# s1, s2 are trimmed copies
[c1, c2] = pu.as_series([c1, c2])

if len(c1) > len(c2):
c = c2
xs = c1
else:
c = c1
xs = c2

if len(c) == 1:
c0 = c[0]*xs
c1 = 0
elif len(c) == 2:
c0 = c[0]*xs
c1 = c[1]*xs
else :
nd = len(c)
c0 = c[-2]*xs
c1 = c[-1]*xs
for i in range(3, len(c) + 1) :
tmp = c0
nd =  nd - 1
c0 = hermesub(c[-i]*xs, c1*(nd - 1))

pol2 = [0]*j + [1]
val2 = herme.hermeval(self.x, pol2)
pol3 = herme.hermemul(pol1, pol2)
val3 = herme.hermeval(self.x, pol3)
assert_(len(pol3) == i + j + 1, msg)
quo, rem = herme.hermediv(tgt, ci)
assert_equal(trim(res), trim(tgt), err_msg=msg)